PERLINDUNGAN HUKUM TERHADAP PEMENANG LELANG SEBAGAI PEMBELI BERITIKAD BAIK YANG DIGUGAT KEMBALI - Putu Eka Trisna Dewi (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2020)
When the bank debtors did not make the payment, the bank as the holder of the mortgage is bound in the credit agreement by obtaining fulfillment of the debtor's credit through an auction process as mandated by law. Problems will arise if the auction winner cannot own or control what he has won because the debtor uses the auction process on the collateral. Then the winner of the auction is a buyer with ‘good faith’ who must be protected by law, and legal protection for the buyer with ‘good faith’ as stated in article 584 of the Civil Code of ‘good faith’ exists if the property rights are obtained through one of the means to obtain property rights, where from that article It is known that some of the transfer of existing property rights cannot be separated from the existence of the agreement law in the Civil Code. Legal remedies that can be taken by the injured parties during the auction execution by the court if there is a rebuttal due to the lawsuit made by the original owner which is later won by the court's decision of the original owner, then the auction holder can submit legal remedies to the high court to resolve the problem by way of an appeal to the Supreme Court. This is because selling through an auction is a civil selling effort and legal remedies that can be taken within the scope of civil law.